(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2024)
Gaming disorder receives increasing attention in the public health arena, but lacks consensus regarding its definition, etiology, and prevalence. This research aimed to investigate the relationship between gaming disorder and genres of preference, platforms of preference (console, computer), modalities (single-player, multiplayer), and impulsive behavior. A total of 100 individuals participated in the research. Data were collected via gamer habit questionnaire, gaming disorder scale (IGDS9-SF), and delay discounting tasks, in monetary and contextual domains. Results indicate that higher frequency of dependence symptoms is associated with preference for the RPG genre, higher levels of impulsive behavior in the contextual domain, younger age, longer weekly playing time, and higher preference for single-player mode. No differences between platforms were identified. We conclude that gender, by itself, is not a good predictor variable of dependence.